Augmenting Anticancer Immunity Through Combined Targeting of Angiogenic and PD-1/PD-L1 Pathways: Challenges and Opportunities - Hack, Stephen P.; Zhu, Andrew X.; Wang, Yulei (Frontiers in Immunology, 2020)
Cancer immunotherapy with antibodies targeting the programmed cell death 1 protein (PD-1)/ programmed cell death 1 ligand 1 (PD-L1) axis have changed the standard of care in multiple cancers. However, durable antitumor responses have been observed in only a minority of patients, indicating the presence of other inhibitory mechanisms that act to restrain anticancer immunity. Therefore, new therapeutic strategies targeted against other immune suppressive mechanisms are needed to enhance anticancer immunity and maximize the clinical benefit of cancer immunotherapy in patients who are resistant to immune checkpoint inhibition. Preclinical and clinical studies have identified abnormalities in the tumor microenvironment (TME) that can thwart the efficacy of PD-1/PD-L1 blockade. Angiogenic factors such as vascular endothelial growth factor (VEGF) drive immunosuppression in the TME by inducing vascular abnormalities, suppressing antigen presentation and immune effector cells, or augmenting the immune suppressive activity of regulatory T cells, myeloid-derived suppressor cells, and tumor-associated macrophages. In turn, immunosuppressive cells can drive angiogenesis, thereby creating a vicious cycle of suppressed antitumor immunity. VEGF-mediated immune suppression in the TME and its negative impact on the efficacy of cancer immunotherapy provide a therapeutic rationale to combine PD-1/PD-L1 antibodies with anti-VEGF drugs to normalize the TME. A multitude of clinical trials have been initiated to evaluate combinations of a PD-1/PD-L1 antibody with an anti-VEGF in a variety of cancers. Recently, the positive results from five Phase III studies in non-small cell lung cancer (adenocarcinoma), renal cell carcinoma, and hepatocellular carcinoma have shown that combinations of PD-1/PD-L1 antibodies and anti-VEGF agents significantly improved clinical outcomes compared with respective standards of care. Such combinations have been approved by health authorities and are now standard treatment options for renal cell carcinoma, non-small cell lung cancer, and hepatocellular carcinoma. A plethora of other randomized studies of similar combinations are currently ongoing. Here we discuss the principle mechanisms of VEGF-mediated immunosuppression studied in preclinical models or as part of translational clinical studies. We also discuss data from recently reported randomized clinical trials. Finally, we discuss how these concepts and approaches can be further incorporated into clinical practice to improve immunotherapy outcomes for patients with cancer.